Superextensions of cyclic semigroups - Gavrylkiv, V.M. (Carpathian Mathematical Publications, 2013)
Given a cyclic semigroup S we study right and left zeros, singleton left ideals, the minimal ideal, left cancelable and right cancelable elements of superextensions λ(S) and characterize cyclic semigroups whose superextensions are commutative.